2010
DOI: 10.1017/s002966511000162x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as anti-inflammatory agents

Abstract: Epidemiological evidence suggests that a high intake of plant foods is associated with lower risk of chronic diseases. However, the mechanism of action and the components involved in this effect have not been identified clearly. In recent years, the scientific community has agreed to focus its attention on a class of secondary metabolites extensively present in a wide range of plant foods: the flavonoids, suggested as having different biological roles. The antiinflammatory actions of flavonoids in vitro or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
285
0
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(332 citation statements)
references
References 62 publications
5
285
0
12
Order By: Relevance
“…Flavonoids and tannins have been reported to inhibit prostaglandin synthesis (Alcaraz & Ferrandiz, 1987). It is ubiquitously known that flavonoids have a great potential as anti-inflammatory agents (Tapas et al, 2008;Tuñón et al, 2009;Serafini et al, 2010). Therefore, we postulated that flavonoids in the extract may correlate appropriately for the present activities.…”
Section: Chan Pit Foong and Roslida Abdul Hamidmentioning
confidence: 86%
“…Flavonoids and tannins have been reported to inhibit prostaglandin synthesis (Alcaraz & Ferrandiz, 1987). It is ubiquitously known that flavonoids have a great potential as anti-inflammatory agents (Tapas et al, 2008;Tuñón et al, 2009;Serafini et al, 2010). Therefore, we postulated that flavonoids in the extract may correlate appropriately for the present activities.…”
Section: Chan Pit Foong and Roslida Abdul Hamidmentioning
confidence: 86%
“…Phytochemical analysis of A. cordifolia indicate that the leaves contain considerable amounts of saponins, alkaloids, and flavonoids (Astuti et al, 2011). It has been reported that flavonoid inhibits inflammatory mediators including TNF-, IL-1 and IL-6, IL-8, and COX-2 (Tunon et al, 2009;Serafini et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of secondary metabolites favors SH seeds to exhibit numerous pharmacological activity. The antidiabetic activity [8], hypolipidemic and antioxidant activity [9], anti-inflammatory [10] of dietary flavonoids are reported earlier.…”
Section: Discussionmentioning
confidence: 99%